Design of The Performance Evaluation of Suppliers at UKM Weedang Uwuh Based on Multi Attribute Decision Making (MADM) - Marni Astuti; Riani Nurdin (Institut Teknologi Dirgantara Adisutjipto, 2020)
The development of small business is increasing with the presence of global competition. The current industrial ecology demands a continuous evaluation process to be able to survive and strive to improve quality products. Weeka Wedang Uwuh continuously improves its business system by paying attention to suppliers of raw materials. Supplier evaluation is carried out to guarantee sustainable quality and performance. Sustainable performance evaluation can produce good judgment if it is supported by a performance appraisal instrument. Supplier performance assessment will be useful to build a good and sustainable relationship between entrepreneurs and suppliers. The design of supplier performance evaluation is carried out using the QCDFR model approach namely, Quality, Cost, Delivery, Flexibility and Responsibility. The sub-criteria study that forms the QCDFR model is carried out using the interview method. QCDFR and Sub Criteria hereinafter referred to as KPI (Key Performance Indicator). KPI is an indicator of ongoing evaluation of the relationship between suppliers and entrepreneurs. The assessment of suppliers from entrepreneurs is carried out using the AHP approach which is able to show the weight of the entrepreneur's assessment of the ability of suppliers. The results of the Weeka Wedang Uwuh supplier performance evaluation model design results in a formulation to measure KPIs with criteria: quality of raw materials (size and condition of raw materials), ease of service (payment tolerance and information on availability and price changes, experience (average transaction value and average) average number of transactions), speed of response (changes in the amount and change in time and price of raw materials). Evaluation of the supplier's weight assessment for raw materials of ginger, sugar and sapphire resulted in the values of Mr. Sarno 0.501, Sugeng 0.709 and Mbak Wang 0.690. KPI measurement reinforces the results of the evaluation of weight assessment using AHP.